2019
DOI: 10.1002/mnfr.201801047
|View full text |Cite
|
Sign up to set email alerts
|

Rising Atmospheric CO2 Lowers Concentrations of Plant Carotenoids Essential to Human Health: A Meta‐Analysis

Abstract: Plant and human tissues (e.g., leaves, retina) share the need for carotenoids to protect against light‐induced and other oxidative stresses. While plants synthesize carotenoids de novo, humans must obtain them primarily through plant‐based foods. In plants, elevated levels of atmospheric carbon dioxide (eCO2) decrease the concentrations of essential minerals, including magnesium and zinc (essential for brain and eye health), but the overall effect of globally rising CO2 levels on carotenoids is unknown. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 98 publications
(101 reference statements)
0
22
1
Order By: Relevance
“…In an experimental study the influence of temperature on total carotenoid content was evaluated and it was found that the total carotenoid content of five tomato varieties was lower at 35.4 °C than at 33.4 °C [ 199 ]. A meta-analysis conducted showed that in general an exposure of plants to high levels of CO 2 decreased the content of carotenoids by 15%, with some exceptions, mainly when the plants were abiotically stressed, in which the concentration of carotenoids increased [ 200 ]. Plantains grown in the south hemisphere contained the more carotenoids provitamin A, α-carotene and β-carotene the greater the incidence of UVB rays [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
“…In an experimental study the influence of temperature on total carotenoid content was evaluated and it was found that the total carotenoid content of five tomato varieties was lower at 35.4 °C than at 33.4 °C [ 199 ]. A meta-analysis conducted showed that in general an exposure of plants to high levels of CO 2 decreased the content of carotenoids by 15%, with some exceptions, mainly when the plants were abiotically stressed, in which the concentration of carotenoids increased [ 200 ]. Plantains grown in the south hemisphere contained the more carotenoids provitamin A, α-carotene and β-carotene the greater the incidence of UVB rays [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
“…The log response ratio eliminates asymmetry between percentage decreases limited to 100% and unlimited percentage increases; it is a standard approach for analyzing elevated [CO 2 ] and other ecological studies [ 112 ]. After performing statistical analyses, all the results were back-transformed to regular percentage changes using the formula: (exp(lnR) − 1)*100%.For estimating the 95% confidence intervals for the mean effect size, a non-parametric test, namely bootstrapping with 999 replacements, was used for sample sizes of seven or more (i.e., when seven or more independent studies reported any given nutrient concentration at low and high treatments) [ 27 ]. The advantage of this approach is that it does not require the distribution of effect sizes to be normal.…”
Section: Methodsmentioning
confidence: 99%
“…Two minerals, Fe and Zn, are already deficient in the diets of hundreds of millions of people, and CO 2 -induced reductions in Fe and Zn have been reported in the edible parts of major crops [ 9 , 22 , 23 ] and are projected to have negative effects on human nutrition [ 24 , 25 ]. Furthermore, emerging evidence points to elevated [CO 2 ] affecting nutrients beyond protein and minerals that are essential to humans, such as vitamins and carotenoids [ 26 , 27 ]. The decrease in mineral concentrations is notable in C 3 plants but less so in C 4 plants [ 9 , 23 ] and is consistent with differences in physiology; the simulation of carbohydrate production by elevated [CO 2 ] is stronger in C 3 plants, while reduced transpiration is present in both C 3 and C 4 plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest a decline in carotenoid content in leaves of different plant species (Dhami et al, 2018). From meta-analysis it was found that CE decreases plant carotenoid concentration by 15% (Loladze et al, 2019). Even though CE is expected to reduce production of reactive oxygen species (ROS) in C 3 plants, Qiu et al (2008) observed increased abundance of leaf protein carbonylation, a potent marker of oxidative stress in Arabidopsis and soybean plants exposed to CE.…”
Section: Introductionmentioning
confidence: 98%